Design : the definitive visual history - Black, Alexandra; Grant, R. G.; Kay, Ann, 1959-; Wilkinson, Philip, 1955-; Zaczek, Iain (DK Publishing, 2015)
Design: The Definitive Visual History is a gorgeous visual celebration of design across the decades. Find out all about the major design movements of the last 150 years from Arts and Crafts to Bauhaus and browse through the beautiful image catalogs of everything from glassware to posters and typography to chairs. Arranged chronologically, from 1850 to the present day, follow the fascinating evolution of how design has influenced the look and functionality of the objects we use every day from telephones and cameras to toys, furniture and fashion. With profiles of iconic designers such as Alvar Aalto, Frank Gehry and Philippe Starck and stunning images of buildings and interiors, Design: The Definitive Visual History is a true celebration of classic design and the perfect package for design lovers.